(3QSGdI ef CMO YdeGA GdeSdejf Edi GdHWQjQc cjQcjQs
(3ChdgG (B:s
(3Ef bOS bOGSI GdSjO cjQcjQ heG gi UaGJg GdeJUa HgG hJYdjd PGJg GdYdjg s
(3BNQgG (B:s
(3SGdekG hai GdMbGFb cdgG HGdjbjf YGdekG Bejf s
(3JMJhi Ydi CSFdI hCLhHJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B_ (3GdeZQH (B(1065 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds